Peripatetic practical lessons on leadership - Amorado, Ronnie V. (Vibal Group, Inc., 2019)
Peripatetic joins the journey in the search for principled leadership—those combined attributes that form a value-laden brand of leadership, that possesses what is good, ethical, qualified, effective and efficient. Principled leadership draws the line in the sand. It is a statement against kakistocratic leadership—those combined elements that create an incompetent, manipulative, unprincipled and unethical leadership.